2016
DOI: 10.1073/pnas.1606608113
|View full text |Cite
|
Sign up to set email alerts
|

IL-33/ST2 signaling excites sensory neurons and mediates itch response in a mouse model of poison ivy contact allergy

Abstract: Poison ivy-induced allergic contact dermatitis (ACD) is the most common environmental allergic condition in the United States. Case numbers of poison ivy ACD are increasing due to growing biomass and geographical expansion of poison ivy and increasing content of the allergen, urushiol, likely attributable to rising atmospheric CO 2 . Severe and treatment-resistant itch is the major complaint of affected patients. However, because of limited clinical data and poorly characterized models, the pruritic mechanisms… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
195
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 211 publications
(210 citation statements)
references
References 44 publications
9
195
1
Order By: Relevance
“…These cytokines are believed rapidly signal barrier breach in order to generate innate immune responses and help prime adaptive immune cells. Strikingly, two recent studies have demonstrated that both TSLP and IL-33 can function as pruritogens (Liu et al, 2016; Wilson et al, 2013a). Additionally, we and others have shown that epithelial cell-derived cytokines are highly expressed in the setting of AD-like disease (Kim et al, 2013; Li et al, 2006; Salimi et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…These cytokines are believed rapidly signal barrier breach in order to generate innate immune responses and help prime adaptive immune cells. Strikingly, two recent studies have demonstrated that both TSLP and IL-33 can function as pruritogens (Liu et al, 2016; Wilson et al, 2013a). Additionally, we and others have shown that epithelial cell-derived cytokines are highly expressed in the setting of AD-like disease (Kim et al, 2013; Li et al, 2006; Salimi et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…In a recent study, the role of peripheral IL‐33/ST2 signaling in a poison ivy‐induced ACD mouse model was illustrated. Inflamed skin‐derived IL‐33 was found to act on ST2, expressed in dorsal root ganglion neurons, and mediate itch (Liu, Tai, et al, ). Also, it is demonstrated that anti‐mouse IL‐33 antibody via subcutaneous injection remarkably reduced the scratching behaviors in the 2,4‐dinitrochlorobenzene‐induced AD mice (Peng et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Although they are less well characterized, non‐immune cells may also constitute important cellular targets of IL‐33 in vivo. These include endothelial cells, epithelial cells, fibroblasts, astrocytes, and neurons …”
Section: Activation Of St2‐expressing Cellsmentioning
confidence: 99%